First report of molecular characterization of Septoria glycines from soybean in Argentina and Uruguay (Aporte Santiaguino, 2025)
Brown spot on soybeans is caused by Septoria glycines Hemmi. The objective of the study was to molecularly analyze the isolates of Septoria glycines in Argentina and Uruguay. These isolates were incubated at 24 ± 2 °C in potato dextrose agar (PDA) for 15 days. Each of the 12 isolates were analyzed by PCR amplification and sequencing of fragments of the internal transcribed spacer region (ITS) and the actin gene (ACT) with the primers: ITS1 / ITS4, ACT-512F / ACT-783R. The results indicate that it was possible to identify 7 and 8 different haplotypes with the target sequences ITS and actin, respectively. The ITS sequences, under the Genbank accession numbers MT162722-MT162733, showed homologies of 98.54 % to 99.38 % with the ITS sequences of S. glycines KU195826.1 from China and AY826767.1 from the USA. Actin sequences MT180168.1-MT180179.1 showed homologies of 97.35 % to 100 % with KF253733.1, previously reported as S. glycines in Japan. High homologies with STIs and actin sequences from other species were also found from China (S. tormentillae-MN150507.1), Japan (S. menthae-KF253780.1), North Korea (S. glycinicola-KF253734.1, S. codonopsidis -KF253689.1) and Iran (S. sonchi-JQ308342.1). However, none of these species was reported as an etiologic agent of soybean brown spot disease. It is concluded that the genetic information confirmed that the isolates belonged to Septoria glycines. This is the first molecular description of the pathogen in South America.
Keywords: Septoria glycines; Soybean; ITS; Actin; Haplotypes